LANGUAGE PATTERNS IN ENGLISH LANGUAGE TEACHING: VIRTUAL EDUCATIONAL DISCOURSE - Natalia Mospan (Borys Grinchenko Kyiv Metropolitan University, 2023)
Distance learning with its virtual settings has launched the transformation of education delivery, pedagogy, and classroom management. Consequently, it could cause educational discourse transformation in higher education as well. The research is focused on revealing educational discourse transformation in distance learning. Besides, the paper answers the following research questions: how university teachers communicate with students in virtual classrooms; what language patterns they use for giving instructions; whether verbal communication between teachers and students has crucially changed in digitally-based education. A mixed method approach (discourse analysis of 12 video-recorded lessons of ESL university teachers and the survey of students (n = 45)) makes it possible to shed light on the state of play in virtual educational discourse. The paper reveals that 1) communication in virtual classrooms depends on pedagogical activities which allows classifying educational language models into the following categories - preparation of teaching material presentation online, student engagement in an activity online, giving instruction on how to use EdTech, and expressing emotions or attitude; 2) university teachers use special language patterns for giving instructions related to using ICT tools and apps, e.g. screen sharing, chatting and emotional modality; 3) verbal communication between teachers and students except for linguistic and extra-linguistic features includes informal modes of communication - chat emojis and signs. The findings highlight that educational discourse has crucially changed in digitally-based education and has transformed into virtual educational discourse. The insights of the paper can contribute to the investigation of virtual educational discourse analysis.